2022
DOI: 10.1101/2022.04.08.22273533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of Illinois’ comprehensive handheld phone ban on talking on handheld and handsfree cellphones while driving

Abstract: Introduction: Distracted driving has been linked to multiple driving decrements and is responsible for thousands of motor vehicle fatalities annually. Most US states have enacted restrictions on cellphone use while driving, the strictest of which prohibit any manual operation of a cellphone while driving. Illinois enacted such a law in 2014. To better understand how this law affected cellphone behaviors while driving, we estimated associations between Illinois' handheld phone ban and self-reported talking on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Because few states implemented handheld phone bans during the study period, we preferred a cross-sectional analysis of the entire data set rather than a quasi-experimental analysis of a data subset. A quasi-experimental analysis of the impacts of Illinois’ handheld phone ban on self-reported talking on handheld, handsfree, and any cellphones while driving was largely consistent with the present study (Benedetti, et al, 2022). Our second limitation was response bias, which can in any occur study of self-reported behavior.…”
Section: Discussionsupporting
confidence: 85%
“…Because few states implemented handheld phone bans during the study period, we preferred a cross-sectional analysis of the entire data set rather than a quasi-experimental analysis of a data subset. A quasi-experimental analysis of the impacts of Illinois’ handheld phone ban on self-reported talking on handheld, handsfree, and any cellphones while driving was largely consistent with the present study (Benedetti, et al, 2022). Our second limitation was response bias, which can in any occur study of self-reported behavior.…”
Section: Discussionsupporting
confidence: 85%